A prospective study of metformin effectiveness as a mammalian target of rapamycin inhibitor and immunoregulator in women with polycystic ovarian syndrome - Moslim Allawi, Asmaa; Waleed Mustafa, Nisreen; Mohammed Hadi, Ali (Journal of Neonatal Surgery, 2025)
Background Polycystic ovarian syndrome (PCOS) is a common disorder affecting ovary function. it’s thought that an autoimmune regulatory mechanism could mediate its onset. Metformin is an effective medication for PCOS treatment and is proposed to act as an immunoregulatory drug. Objective The present work aimed to study the effectiveness of metformin as a mammalian target of rapamycin (mTOR) inhibitor and immunoregulator in PCOS women. Subjects and Methods A total of 80 blood samples were collected, 30 of them from newly diagnosed PCOS women. Once more, blood samples were taken from them following 500 mg of metformin treatment period. In addition, 20 healthy women enrolled as a control group. The levels of mTOR, IL6, and TGFβ1 were measured using the ELISA technique. Results The present work showed that after metformin treatment, levels of mTOR and TGFβ1 dropped significantly, but IL6 levels remained constant. Patients on longer-term metformin treatment experienced a significant decrease in mTOR and TGFβ1 levels, but TGFβ1 remained higher than in healthy controls. No significant differences were found in IL6 levels between treatment duration groups and the body mass index (BMI) groups, according to Spearman correlation, there were no correlation found between mTOR and other studied marker neither pre nor post treatment groups. Conclusion This study concluded that metformin has pleiotropic effects on immune reprogramming due to its role as an mTOR inhibitor and immune modulation of regulatory cytokines.